Technology implementation in care practices for community-dwelling older adults with mild cognitive decline: Perspectives of professional caregivers in Quebec and Brussels. (November 2022) - Dequanter, S; Steenhout, I; Fobelets, M; Gagnon, MP; Sasseville, M; Bourbonnais, A; Giguère, A; Ndiaye, MA; Lambert, A; Gorus, E; Buyl, R
Objective: As worldwide population aging is accelerating, innovative technologies are being developed to support independent living among community-dwelling older adults with mild cognitive decline. However, the successful implementation of these interventions is often challenging. Until now, literature on implementation issues related to the specific context of older adults with mild cognitive decline is lacking and the few studies available do not focus specifically on the perspective of professional caregivers. Yet the perspective of these caregivers is important as they can be considered a key facilitator for technology implementation among this population. Therefore, this study was the first to examine technology implementation among community-dwelling older adults with mild cognitive decline from the broader perspective of professional caregivers. Methods: In this qualitative study, two focus groups consisting of a heterogeneous pool of professional caregivers were conducted: one in Quebec (Canada, n  = 6) and one in Brussels (Belgium, n  = 8). Braun and Clarke' method for thematic analysis, guided by a qualitative descriptive approach was applied to inductively identify themes from the data. Results: We identified factors influencing technology implementation in older adults with mild cognitive decline on three levels: an individual level (e.g., characteristics of older adults with mild cognitive decline and professional caregivers' attitude), an organizational level (e.g., lack of training among professional caregivers) and a level referring to the broader context (e.g., ethical considerations). Conclusions: This study contributes to the research gap in knowledge on the needs of professional caregivers to facilitate technology implementation among the population of older adults with cognitive decline. Future directions for research, practice, and policy are given, more specifically to improve knowledge among caregivers and on the development of decision support to retrieve safe and effective technologies that suit patient-centered care.